The study of G-quadruplex in supercoiled DNA - Lv, Bei (2016)
It is demonstrated that DNA gyrase, an essential bacterial enzyme which possesses a unique ability to introduce negative supercoils into DNA, can drive G-quadruplex generation from plasmid DNA under the intracellular concentrations of cations in prokaryotes. The outcomes of our investigations could suggest that prokaryotic cells might utilize this topological enzyme to regulate generation of a G-quadruplex to comply with their subsequent cellular functions. On the other hand, our in vitro studies also show that both breakdown of some thermodynamically stable non-B structures and resumption of B-conformation of DNA can take place during the courses of isothermal helicase-dependent amplification (HDA). We speculate that the pathway of making the non-B structures repairable is the relieving of accumulated torsional stress that is caused by the positive supercoiling. Our findings suggest that living organisms might have evolved this distinct and economical pathway for repairing their physically altered DNA structures.